What gender/kind of university in Italy? Educational persistence and best practices for the Gender Equality (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Gender equality, as a principle enshrined in the Italian Constitution, has imposed itself with new vigour as a goal for education in all school and university cycles in the 2030 Agenda, launched by the United Nations in 2015 for a sustainable development. Recent analyses of the Italian education system, and of the university in particular, have revealed many critical issues, inequalities and still wide gaps from the sustainability goals: balancing the presence of women and men in research, evaluation and selection activities, in boards and commissions and in the lists of experts. It is precisely in teaching activities that there seems to be most resistance to including gender as a cross-cutting factor in course programmes. While the consequences are already being studied, the causes are often identified as cultural factors. A review of practices and devices will be followed by an exploration of the presence of gender in the teaching experiences of Italian universities. The aim is to highlight good practices and their application in international educational systems, with tools such as the Gender Equality in Academia and Research - GEAR tool of the EIGE and of bodies that regulate the classifications of research areas (ERC, UNESCO etc), including the gender factor as an autonomous and transversal one.
Keywords: gender; academic education; gender equality; transversal; best practices